Design And E-Voting Information System Based Web Using E-Ktp On Election Of The Head Of City Of Semarang - Rina Dwi Yunita Sari (JAICT, 2018)
Elections of regional heads is the local election process is based on a majority vote. While voting (voting) is one of the stages of elections. A common problem that occurs in the general election that the election and the collection of voters who still use manual way. In this final project designed an election system by taking these problems. The system designed is a system of e-voting. E-voting system is a method of polling / voting by electronic media and the Internet, making it easier and speed up the selection process. The system can be minimized by using e-KTP and fingerprint identification as data validation as well as a web-based information that is easily accessible to users and the public in obtaining information related to the implementation of e-voting.